Clinical utility of circulating miR-371a-3p for the management of patients with intracranial malignant germ cell tumors. Issue 1 (13th April 2020) - Murray, Matthew J; Ajithkumar, Thankamma; Harris, Fiona; Williams, Rachel M; Jalloh, Ibrahim; Cross, Justin; Ronghe, Milind; Ward, Dawn; Scarpini, Cinzia G; Nicholson, James C; Coleman, Nicholas
Abstract: Background: The current biomarkers alpha-fetoprotein (AFP) and human chorionic gonadotropin (HCG) have limited sensitivity/specificity for diagnosing malignant germ cell tumors (GCTs) and "marker-negative" patients require histological confirmation for diagnosis. However, GCTs at intracranial sites are surgically relatively inaccessible and biopsy carries risks. MicroRNAs from the miR-371 373 and miR-302/367 clusters are over-expressed in all malignant GCTs and, in particular, miR-371a-3p shows elevated serum levels at diagnosis for testicular disease. Methods: Using our robust preamplified qRT-PCR methodology, we quantified miR-371a-3p levels in serum and cerebrospinal fluid (CSF) in a series of 4 representative clinical cases, 3 with intracranial malignant GCT and 1 with Langerhans cell histiocytosis (LCH), compared with appropriate control cases. Results: Serum and/or CSF miR-371a-3p levels distinguished those with intracranial malignant GCTs from LCH and, if known in real time, could have helped clinical management. The benefits would have included (1) the only confirmatory evidence of an intracranial malignant GCT in 1 case, supporting clinical decision making; (2) early detection of intracranial malignant GCT in another, where an elevated CSF miR-371a-3p level preceded the histologically confirmed diagnosis by 2 years; and (3) confirmation of an intracranial malignant GCT relapse with an elevated serum miR-371a-3p level, where serum and CSF AFP and HCG levels were below thresholds for such a diagnosis. Conclusions: This series highlights the potential for microRNA quantification to assist the noninvasive diagnosis, prognostication, and management for patients with intracranial malignant GCTs. Serum and CSF should be collected routinely as part of future studies to facilitate the extension of these findings to larger patient cohorts.